Issues and challenges of technical and vocational education and training in Malaysia towards human capital development - Ismail, Affero; Zainal Abiddin, Norhasni (IDOSI Publications, 2014)
To become a high-income economy, skilled workforce is vital. Under the concept of Human Capital Development (HCD), it is vital to provide effective training and education especially in technical and vocational education. The injection of education acquisition to the trainees will increase the performance, productivity and capability which translates into a good investment. As a result, it is important to increase the enrolment in Technical and Vocational Education and Training (TVET) and raise the overall training quality since TVET has become crucial in these recent years for industries and the economy as a whole. This paper will discuss the overview and the course of TVET in Malaysia. The main thrust of this paper is to highlight the challenges that overlay the implementation of TVET in Malaysia. Hence, the development of Knowledge Worker (K-worker) and human capital will be realized.